A study of demographic profile of HIV positive patients attending ART centre SGMH Rewa, Madhya Pradesh - Rajkumar Upadhay; Omprakash Nayak (International Journal of Medical Research and Review, 2019)
Background: Caused by Human Immuno-deficiency virus, leading the patient’s immune system vulnerable to various infections and neurological disorder, AIDS have transformed into a socioeconomic and developmental concern. With the increasing population of India, the HIV epidemic will soon be a major cause of concern. The objective of the present study was to observe the demographic profile of HIV positive patients attending ART Centre at the Department of Medicine at Sanjay Gandhi Memorial Hospital & Shyam Shah Medical College, Rewa (M.P.) in year 2012-2014.Material & Methods: This was a data-based study. In this study total 1224 cases of all age group were taken, these patients were registered in ART center in between Jan. 2010 to Dec.2012. A pre-formed questionnaire (proforma) was made to enquire about socio-demographic-economic variables. The patient and their spouse were interviewed, examined and investigated according to pre-designed proforma with special reference to their occupation, spouse HIV status and high-risk behaviour.Results: In this study total number of ART attendees (patients) were 1224 and out of these total patients, 7.27% (n=89) were children (<15years) and 92.73% (n=1135) were adult (>15 years). Out of 89 children, 5.15% (n=63) were male and 2.12% (n=26) were female and out of 1135 adult patients, 53.26% (n=652) were male and 39.46% (n=483) were female. M/F ratio in children was 2.4/1 and M/F ratio in adult patients was 1.3/1.Conclusion: As the present study was done in rural area, where hygiene was poor and sanitation was bad and environment was dusty, that is why infectious complications were more common in the present study.